Perforated Jejunal Wind Sock Anomaly - Özel, Ş. Kerem; Köseoğulları, A. Aysel; Kazez, Ahmet; Özercan, İbrahim H. (Fırat University, 2003)
Aim: In this study a case of wind sock anomaly is presented due to its rare localization. Case: A 10 days old girl with Down syndrome was brought to our unit with the complaint of bilious vomiting. Triple air-fluid levels in the epigastric region and scarce gaseous images in the distal intestinal system were detected in the upright abdominal X-ray. The patient was operated with the diagnosis of proximal intestinal obstruction. Perforated wind sock anomaly was detected in the proximal jejunum. Membrane ablation and primary repair was done. Pathological examination revealed jejunal mucosa in the membrane. Conclusion: Wind sock anomaly in the proximal jejunum was not reported in the literature before. The probability that this types of anomalies can be detected in the gastrointestinal system other than duodenum is emphasized.

Amaç: Bu çalışmada klasik yerleşimi dışında saptanan perfore "wind sock" anomalili bir olgu nadir lokalizasyonu nedeniyle sunulmuştur. Olgu: Down sendromu olan 10 günlük kız olgu, safralı kusma şikayeti ile kliniğimize getirildi. Ayakta direkt karın grafisinde epigastrik bölgede üçlü gaz görünümü ve distalde az miktarda gaz dağılımı saptandı. Hasta parsiyel proksimal intestinal obstrüksiyon ön tanısıyla ameliyat edildi. Operasyonda Treitz ligamanının distalinde, proksimal jejunumda perfore membranlı "wind sock" anomalisi saptandı ve membran eksizyonu yapılarak primer onarım uygulandı. Patolojik incelemede membranda jejunal mukoza görüldü, duodenuma ait mukozal yapılara rastlanmadı. Sonuç: Bu vakada saptadığımız proksimal jejunumdaki "wind sock" anomalisi, daha önce literatürde tarif edilmemiştir. Bu anomalinin sadece duodenuma ait olmadığı, literatürdeki vaka ile beraber değerlendirildiğinde intestinal sistemin diğer kısımlarında da saptanabileceği vurgulanmak istenmiştir.
Jejunal Yerleşimli Perfore Wind Sock Anomalisi